Dual blockade of epidermal growth factor receptor and insulin‐like growth factor receptor–1 signaling in metastatic pancreatic cancer: Phase Ib and randomized phase II trial of gemcitabine, erlotinib, and cixutumumab versus gemcitabine plus erlotinib (SWOG S0727). Issue 19 (16th July 2014) - Philip, Philip A.; Goldman, Bryan; Ramanathan, Ramesh K.; Lenz, Heinz‐Josef; Lowy, Andrew M.; Whitehead, Robert P.; Wakatsuki, Takeru; Iqbal, Syma; Gaur, Rakesh; Benedetti, Jacqueline K.; Blanke, Charles D.
<x xml:space="preserve">Abstract</x> BACKGROUND Targeting a single pathway in pancreatic adenocarcinoma (PC) is unlikely to affect its natural history. We tested the hypothesis that simulataneous targeting of the epidermal growth factor receptor (EGFR) and insulin‐like growth factor receptor–1 (IGF‐1R) pathways would significantly improve progression‐free survival (PFS) by abrogating reciprocal signaling that promote drug resistance METHODS This was a phase Ib/II study testing cixutumumab, combined with erlotinib and gemcitabine (G) in patients with untreated metastatic PC. The control arm was erlotinib plus G. The primary end point was PFS. Eligibility included performance status 0/1 and normal fasting blood glucose. Polymorphisms in genes involved in G metabolism and in the EGFR pathway were also studied RESULTS The phase I results (n = 10) established the safety of cixutumumab 6 mg/kg/week intravenously, erlotinib 100 mg/day orally, and G 1000 mg/m2 intravenously on days 1, 8, and 15 of a 28‐day cycle. In the RP2 portion (116 eligible patients; median age, 63), the median PFS and overall survival (OS) were 3.6 and 7.0 months, respectively, on the cixutumumab arm, and 3.6 and 6.7 months, respecively, on the control arm. Major grades 3 and 4 toxicities with cixutumumab and control were elevation of transaminases, 12% and 6%, respectively; fatigue, 16% and 12%, respectively; gastrointestinal, 35% and 28%, respectively; neutropenia, 21% and 10%, respectively; and thrombocytopenia, 16% and 7%, respecively. Grade 3/4 hyperglycemia was seen in 16% of patients on cixutumumab. Grade 3 or 4 skin toxicity was similar in both arms of the study (< 5%). No significant differences in PFS by genotype were seen for any of the polymorphisms. CONCLUSIONS Adding the IGF‐1R inhibitor cixutumumab to erlotinib and G did not lead to longer PFS or OS in metastatic PC. Cancer 2014;120:2980–2985. © 2014 American Cancer Society.